Application of Design of Experiments for Catalytic Oxygen Removal over Pt/γ‐Al2O3 Catalyst. Issue 10 (30th August 2022) - Suh, Sung Youn; Geitner, Christian; Hänel, Marvin; Wiesmann, Thomas; Watermann, Clara Maria; Lohmann, Heiko; Apfel, Ulf‐Peter; Zeidler‐Fandrich, Barbara
Abstract: The following orientational study uses a factorial experimental design (DoE) strategy to determine the influence of different process parameters on the catalytic removal of oxygen traces (4500–9000 ppmv O2 ) from coke oven gas by commercial Pt/ γ ‐Al2 O3 . Along this line, various experiments have been performed from 1 up to 11 bar and 150–250 °C with a gas hourly space velocity between 20 000 and 25 000 h −1 . The statistical analysis demonstrates that the applied temperature and pressure have a significant impact on the oxygen removal process. Experiments using gas mixtures with additional 350 ppmv H2 S indicate a deactivation of the catalyst with a 66 % oxygen conversion at 250 °C and 6 bar. The close agreement between predicted and experimental data highlights the efficient approach for optimizing the oxygen removal from coke oven gas utilizing DoE strategies. Abstract : The catalytic oxygen removal from coke oven gas (COG) was investigated by design of experiments. Various process parameters, namely, temperature, pressure, O2 concentration, and gas hourly space velocity, and the impact of the catalyst poison H2 S were evaluated. This provides an approach to optimize the process conditions in the field of COG utilization.